2021
DOI: 10.1002/eco.2294
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater subsidizes tree growth and transpiration in sandy humid forests

Abstract: As drought variability increases in forests around the globe, it is critical to evaluate and understand ecosystem attributes that ameliorate drought impacts. Trees in arid and semi‐arid ecosystems can sustain tree growth and transpiration during drought by accessing shallow groundwater, yet the extent to which groundwater influences forest growth and transpiration in humid environments has largely been unexplored. We quantified groundwater's influence on tree growth and transpiration in northern humid forests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 76 publications
0
18
0
Order By: Relevance
“…Even humid regions are subject to droughts (e.g., Schubert et al, 2021; Seager et al, 2009), and, while they often are of shorter duration compared with more arid regions like the Western United States, they can induce vegetation stress and mortality (Berdanier & Clark, 2018, 2016). Ciruzzi and Loheide (2021) demonstrated that when trees in a humid region could access shallow groundwater, greater growth occurred, thus suggesting that a better understanding of groundwater–tree interactions in humid regions could improve riparian zone management.…”
Section: Introductionmentioning
confidence: 99%
“…Even humid regions are subject to droughts (e.g., Schubert et al, 2021; Seager et al, 2009), and, while they often are of shorter duration compared with more arid regions like the Western United States, they can induce vegetation stress and mortality (Berdanier & Clark, 2018, 2016). Ciruzzi and Loheide (2021) demonstrated that when trees in a humid region could access shallow groundwater, greater growth occurred, thus suggesting that a better understanding of groundwater–tree interactions in humid regions could improve riparian zone management.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that greater emphasis on how plants interact with the belowground environment (Warren et al, 2015), and considering the entire critical zone from aquifers to treetop is needed (Dawson et al, 2020) to develop accurate predictions of ecosystem responses to climate change. Tree roots may delve deep enough below the surface to reach aquifers (Jackson et al, 2000; Miller et al, 2010), which can backstop water availability during exceptionally dry conditions to sustain the ecosystem (Baldocchi et al, 2021; Ciruzzi & Loheide II, 2021; Domec et al, 2010; Montaldo & Oren, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Ground-based ecological data to compare to drought indicators can be difficult to obtain, but tree-ring records have proven valuable in forests across a wide range of climatic conditions (Bhuyan et al, 2017), even in humid environments (Ciruzzi & Loheide, 2021).…”
Section: A Common Meteorological Drought Indicator Is Palmer Droughtmentioning
confidence: 99%
“…Ground‐based ecological data to compare to drought indicators can be difficult to obtain, but tree‐ring records have proven valuable in forests across a wide range of climatic conditions (Bhuyan et al, 2017), even in humid environments (Ciruzzi & Loheide, 2021). Variations in annual tree‐ring widths indicate growth response to drought at the individual‐tree or stand scale (Camarero et al, 2015), while remote‐sensing imagery provides information on photosynthetic activities from stand to forest scales.…”
Section: Introductionmentioning
confidence: 99%